Performance gains from directional antennas in full-duplex systems - Psomas, Constantinos; Skouroumounis, Christodoulos; Krikidis, Ioannis; Kalis, Antonis; Theodosiou, Zenonas; Kounoudes, Anastasis (My University, 2015)
Full-duplex (FD) radio can potentially provide a higher spectral efficiency provided the self-interference (SI) at a terminal can be substantially mitigated and the multiuser interference, in the case of a large-scale scenario, is restricted. In this paper, we investigate the positive impact directional antennas can have on the reduction of these two types of interference. We study a two-dimensional geometric channel model in order to understand and acquire insight regarding the multipath effects on the SI caused by scatterers. Moreover, we provide a performance analysis for the uplink in large-scale FD cellular networks and model the impact of passive suppression on the network's performance. The derived results show the significant performance gains that can be achieved by the employment of directional antennas.
Keywords: Full-duplex; Directional antennas; Cellular networks; Channel model